Recruitment of Village Apparatus in the Regions and Implementation - Suwari Akhmaddhian (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2019)
The purpose of this article is to find out how the rules for the appointment of a village apparatus in the area and to know the implementation of the appointment at every level of village apparatus in the area. The research method used is empirical normative data collection through literature study, observation and interviews. The research location is Kuningan Regency, West Java. The results of the study are that the regulation on the selection of village apparatus is regulated in Law Number 6 of 2014 concerning Villages while the implementation of the local government issued Regional Regulation of Kuningan Regency Number 13 of 2015 concerning Village Apparatus and Kuningan Regent Regulation Number 73 of 2015 concerning Procedure for Appointment, Dismissal and Transfer of Position of Village Apparatus. Factors that predominantly influence the implementation of the appointment of the village apparatus are the lack of community knowledge related to regulations related to the selection of village apparatus so that there is a need for educational activities to the community related to regulations at the regional level.